Reinforcement of Teeth Having Reenacted Perforating Internal Resorption Cavities After Repair Using Different Calcium Silicate-based Cements and Backfilling Materials: An In vitro Study - Bansal Manu; Bhardwaj Anuj; Bhardwaj Amit (Wolters Kluwer Medknow Publications, 2024)
To evaluate the fracture resistance (FR) of the teeth having reenacted perforating internal resorption cavities repaired by distinctive calcium silicate-based cements (CSCs) specifically: Endocem MTA, Biodentine, NeoMTA Plus, and backfilling materials. Ninety-six freshly extracted human mandibular premolar teeth were selected. Twelve roots were used as the negative control group. Rotary files were used to complete the final irrigation and root canal preparation on the remaining teeth. Following that, burs were used to make standardized internal resorption chambers in the middle part of the roots. Twelve of these samples were used as positive control samples. The remaining 72 root canals were obturated in the apical 4 mm using a single-cone approach, and they were separated into 6 groups based on the CSCs used to fill voids and the materials used as backfilling. Group 1: Endocem MTA (resorption) + Endocem MTA (coronal), Group 2: Endocem MTA (resorption) + Gutta-percha/sealer (coronal), Group 3: Biodentine (resorption) + Biodentine (coronal), Group 4: Biodentine (resorption) + Gutta-percha/sealer (coronal), Group 5: NeoMTA Plus (resorption) + NeoMTA Plus (coronal), and Group 6: NeoMTA Plus (resorption) + Gutta-percha/sealer (coronal). Specimens were inserted in acrylic resin and then subjected to fracture testing. Fracture strength tests were performed using a Universal Testing Machine. The force was employed vertically with a consistent speed of 1 mm/minute. The results were analyzed with Variance and Bonferrini tests at P < 0.005. The mean force of fracture values were 447.00, 201.25, 318.75, 187.50, 596.58, 258.75, 347.50, and 298.75 N for Group 1, 2, 3, 4, 5, 6, 7, and 8, respectively. "There was a significant difference (P < 0.001) between the experimental groups and the control group". Group 5 showed the highest FR as compared to other groups. Backfilling with CSCs appears to be a better material than a gutta-percha/sealer combination. Neo MTA plus furthermore appeared the highest fracture-resistant material, while Biodentine + Gutta percha/sealer showed the least FR.